STUDENTS' RESPONSES OF JOYFUL LEARNING CLASS IN ISLAMIC ELEMENTARY SCHOOL: FLASHCARD GAMES AND VISUAL WORKSHEET - Donasari, Renita; Rofiah, Tutik Dinur; Qurroti, Athi’illah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2023)
The four characteristics of young learners, which can be embodied in learning that is active, fun, concrete, and uses sensory experiences, should be considered to optimize vocabulary learning. Therefore, this qualitative research aims to investigate students' responses to the joyful vocabulary class by implementing flashcard games and visual worksheets. The instruments used were a Likert scale questionnaire, interviews, observation, and documentation, with 20 students in the second grade of SD Sunan Ampel Kediri acting as respondents selected using purposive sampling. The results showed positive student responses to the Joyful Vocabulary Learning Class. This approach not only encourages active participation, motivation, and fun in learning vocabulary but also enables students to remember vocabulary easily and understand its meaning due to the combination of concretizing the abstract with the sense of sight by visualizing through pictures of animals and creating an active and fun class in the form of games. In conclusion, the use of flashcard games and visual worksheets to promote a joyful vocabulary class can be used to teach English to young learners.